The Study of Graffiti (wall and desk writings) of Junior High School Students based on Description, Interpretation and Explanation of Critical Discourse Analysis - Gholamreza Rostami; Haniyeh Davatgari Asl; Nader Asadi (Iranian Journal of Educational Research)
Objective:The purpose of this research is to study the wall and desk writings from the linguistics aspects to reach students underlying and hidden layers of text, namely the relationship between power and ideology. And it brings together various ideologies within the text to achieve critical deconstruction. Method: For this, the method of critical discourse analysis of Fairclough was used. A descriptive content analysis method was used. The data of this study is 40 writings of various  junior high school students in Miyandoab. These writings were taken by camera and also was used note taking. Results:This research was analyzed by using of the framework of critical discourse analysis approach in three layers of description, interpretation and explanation. At the descriptive level, more emphasis is placed on the lexical items and metaphorical aspects that express the students ideological perspective. At the level of interpretation, the emotional, psychological crisis and the limitations prevailing in schools and different discourses are interpreted with an intertextual connection. At the explanation stage, distress, hatred, feelings, friendship and hostility all express the emotions of the students. The position of the teacher and manager in relation to the students and their power are expressed. Conclusion: The results showed that  power of teachers ,managers and the ruling of  ideology in schools caused the students to write their thoughts on the desks and walls and express the ruling discourse in school.